Dampak Pola Asuh Orang Tua terhadap Perkembangan Remaja: Sebuah Studi Kepustakaan - Nisa, Amilia Khoirun; Sulistyowati, Alya Putri; Viananda, Davin Maulana; Kinasih, Hanna Astrid; Wibowo, Agasetya; Makhmudah, Ulya (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2025)
Parenting patterns are a form of parental care for children and how parents behave in educating, guiding, disciplining and protecting children to reach the maturity process and fulfill children’s development tasks in accordance with the norms and values that apply in society. Parenting patterns are important, especially during adolescence is a transition period from childhood to adulthoold. The types of parenting provided by parents include authoritarian, permissive and democratic parenting. This research aims to determine the form of parenting patterns and the impact of the parenting patterns provided by parents on adolescents. This research method uses Systematic Literature Review (SLR) by collecting 20 journal articles and analyzing the data sources from these journal articles. The result of the research that has been carried out show that the perfect form of parenting is how parents guide their children appropriately and in a balanced way, as well as adapting them to the children’s needs and conditions in order to maximize their development potential.